Synthesis, Characterization & Screening for Anti-Inflammatory & Analgesic Activity of Quinoline Derivatives Bearing Azetidinones Scaffolds - Kumar Gupta, Sujeet; Mishra, Ashutosh (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2016)
Background: Non-steroidal anti-inflammatory drugs (NSAIDS) are clinically used as anti-inflammatory, analgesic and antipyretic agents but they have the drawbacks such as gastric irritation and gastric ulceration. Recently, quinoline derivatives have shown significant anti-inflammatory and less ulcerogenic activity. The present study deals with the synthesis and pharmacological assessment of a series of novel quinoline derivatives bearing azetidinones scaffolds as anti-inflammatory and analgesic agents. Methods: A series of newer 3-chloro-1-(substituted)-4-(tetrazolo [1,5-a]quinolin-4- yl)azetidin-2-one derivatives (6a-l) was synthesized starting with acetanilide (1). Initially, acetanilide (1) was allowed to react with Vilsmeier-Haack reagent (DMF + POCl3) to form 2- chloro-3-formyl quinoline (2). The 2-chloro-3-formyl quinoline (2) was further treated with p-toluenesulphonic acid and sodium azide which yielded Tetrazolo [1,5-1] quinoline-4- carbaldehyde (3). The reaction of formyl group with various substituted amines (4a-l) formed corresponding Schiff base intermediates (5a-l), which were further allowed to react with chloroacetyl chloride to produce 3-chloro-1-(substituted)-4-(tetrazolo [1,5-a]quinolin-4-yl) azetidin-2-one derivatives (6a-l). The structure of the final analogues (6a-l) has been confirmed on the basis of elemental analysis, IR, 1H NMR, 13C NMR and mass spectra. All the synthesized compounds were evaluated for their anti-inflammatory and analgesic activities by using carrageenan induced rat paw model and Eddy’s hot plate method respectively. Results: All the values of elemental analysis, IR, 1H NMR, 13C NMR and mass spectra were found to be prominent. The anti-inflammatory activity test revealed that 3-chloro-1-(4-methoxyphenyl)- 4-(tetrazolo[1,5-a] quinolin-4-yl)azetidin-2-one (6b), 3-chloro-1-(2-methoxyphenyl)- 4-(tetrazolo[1,5-a]quinolin-4-yl)azetidin-2-one (6a) exhibited significant anti-inflammatory and analgesic activity as compared to control group. Conclusion: The results of the current study indicate that substitution at quinoline derivatives bearing azetidinones scaffolds showed potent analgesic and anti-inflammatory activities.
Keywords: Quinoline